OVERVIEW ABOUT THE MANAGEMENT OF THE HUMAN RESOURCE IN PROJECTS - Drob, Catalin (Studies and Scientific Researches. Economics Edition, 2015)
The purpose of this study is to emphasize the main aspects regarding the management of the human resource in projects. This study tries to present in the comparative manner, different approaches of several guidelines, international standards and methodologies regarding the management of the human resource in projects (the PMBOK ® Guide elaborated by the Project Management Institute and the PRINCE method elaborated by the British Office of Government Commerce). The PMBOK® Guide describes four elements (processes) of human resource management: human resource planning, acquire project team, develop project team and manage project team. The PMBOK approach regarding human resource management is focused on utilizing the people involved in the project in the best way. According the PRINCE method the management of the human resource is focused on the roles and responsibilities of the human resource within the project. In this standard, the responsibilities are viewed like a roles. Everybody involved in the project can have one or more roles and a role can be fulfilled by several persons.